Effect of motor control exercises on psychological variables in chronic low back pain in computer professionals - ARUN BALASUBRAMANIAM; MAHADEVI BHARATHI (International Journal of Pharma and Bio Sciences, 2016)
An 80% of individuals in the world suffer with low back pain and 76% of computer users suffer with various musculoskeletal disorders. Reasons for these disorders are poor posture, use of awkward sitting and static positioning for longer duration. Studies have addressed on the management of low back pain but, lack of evidences. Purpose of the study is to determine the effect of motor control exercises on psychological variables in chronic low back pain in computer professionals. 44 subjects with chronic low back pain were selected using convince sampling method and they all included upon assessment and based on selection criteria. Experimental group underwent motor control exercises based on O’Sullivan and Moseley protocols, where as Home exercises were advised to the control group. Outcomes measured were Roland Morris disability index for functional disability and Beck depression inventory for psychological variable. Results were analysed using student ’t’ test, it found 23.67 (P< 0.05%) for the Beck depression inventory and 5.40 (P< 0.05%) Roland morris disability index. The study concludes the experimental group show greater reduction in disability and depression when compared with the control group.